(untitled) (Journal of Engineering, 2024)
The important way to obtain lightweight concrete with compressive strength, density, and thermal insulation properties that differ from normal concrete was by adding materials with cementitious properties to the concrete mix instead of cement or using lightweight aggregate. In most cases, the compressive strength of the lightweight concrete produced was less than that of normal concrete. The aim of this research was to conduct three main objectives. The first objective is to produce lightweight concrete with good compressive strength compared to the same type of concrete by adding chemical additives (Super-Plasticizer S.P and Carbon Powder C.P) to the lightweight concrete mix. The second objective is to recycle the residues of the local brick and use them as coarse aggregates in the production of lightweight concrete. The third objective is to increase the thermal insulation rate of concrete by adding the same r additive. The results were good, concrete was produced from this work with the lowest density of up to (1810 kg/m3) and the highest compressive strength of up to (31.240 MPa) when only carbon powder was added in certain proportions and the density of up to (1944 kg/m3) and compressive strength of up to (31.946 MPa) when adding (Super-Plasticizer) to the same percentages of carbon powder. Compared to ordinary lightweight concrete without chemical additives, its density reaches (1894 kg/m3) and compressive strength (24.848 MPa) at the age of 28 days. In addition, the thermal conductivity values reached about (0.507 W/m.oC), compared to ordinary lightweight concrete (2.242 W/m.oC).